Constructivism-Based Hand Puppet Role-Playing to Improve Children’s Emotional Regulation Skills - Mirna Sari; Aini Mahabbati (MASI Mandiri Edukasi, 2026)
Emotional regulation difficulties among early childhood learners, particularly those with emotional disorders, require instructional strategies that are developmentally appropriate and engaging. This study aimed to enhance children’s emotional management abilities through constructivism-oriented hand puppet role-playing activities. The research employed Classroom Action Research, combining qualitative and quantitative descriptive approaches. It was conducted with 11 children in Group B2 at TK Negeri 2 Kaubun during the second semester of the 2024/2025 academic year, with a focused observation of three children identified as having difficulties with emotional regulation. The research procedure followed four iterative stages: planning, action implementation, observation, and reflection. Data were obtained through systematic observation of emotional regulation indicators, behavioral responses, and participation during learning activities. The findings demonstrated a marked improvement in children’s emotional management skills after the intervention. The mean achievement score increased from 44.8% in Cycle I, categorized as Beginning to Develop, to 77.1% in Cycle II, classified as Developed as Expected. Improvements were evident across four aspects: recognizing personal and others’ emotions, expressing emotions appropriately, strengthening self-confidence, and demonstrating positive social behavior. These results indicate that constructivist hand-puppet role-playing is an effective pedagogical medium for supporting children’s ability to recognize, express, and regulate emotions in constructive and social ways.